Access to water and COVID-19: a regression discontinuity analysis for the peri-urban areas of metropolitan Lima, Peru - Gómez-Lobo, Andrés (2024)
This paper presents the results of a quasi-experimental study using information collected through a survey conducted in peri-urban areas of metropolitan Lima and applied to households residing close to and on both sides of the geographic boundary of piped water supply. We find that access to piped water was associated with a reduction in the probability of contracting COVID-19. Furthermore, the results suggest that a minimum consumption level must be guaranteed to lower infection probability. These results highlight the need for investment in infrastructure to close access gaps and the importance of ensuring quality and affordable services for the population.